Superconductivity under uniaxial tensile strain on internal reinforced Nb3Sn multifilamentary wire using Cu-Sn-Zn ternary alloy matrix. (April 2019) - Hishinuma, Yoshimitsu; Oguro, Hidetoshi; Taniguchi, Hiroyasu; Awaji, Satoshi; Kikuchi, Akihiro
Abstract: The degradations of superconducting properties by mechanical strain on actual Nb3Sn wire are a serious problem for the future fusion magnets operated under high electromagnetic force. Recently, we succeeded to fabricate Cu-Sn-Zn ternary alloy matrix, which is high strength alloy by the Zn solid solution strengthening, based on the internal reinforced bronze process in order to investigate the mechanical strength improvement. In this study, the upper critical magnetic field ( H c 2 ) under uniaxial tensile deformation on several bronze-processed Nb3 Sn multifilamentary wires were evaluated. We confirmed that the peak tensile strain values, which obtained maximum H c 2 under uniaxial tensile deformation, were shifted to higher tensile strain region with increasing amount of Zn composition in the Cu-Sn-Zn ternary alloy matrix. The internal reinforced bronze matrix via solid solution strengthening would become attractive and simple method without reinforcement material.